2013
DOI: 10.12912/23920629/310
|View full text |Cite
|
Sign up to set email alerts
|

The Application of the River Habitat Survey Method to the Assessment of the Quality of the River Wardynka (North-Western Poland)

Abstract: Streszczenie. W pracy przedstawiono klasyfikację stanu ekologicznego rzeki Wardynka według metody River Habitat Survey. Badania prowadzono w ramach projektu pt. Przeprowadzenie oceny stanu zasobów przyrodniczych zlewni rzeki Iny w ramach projektu LIFE+: "Budowa niebieskiego korytarza ekologicznego wzdłuż doliny rzeki Iny i jej dopływów" finansowanego ze środków Wspólnoty Europejskiej instrumentu finansowego LIFE+ oraz Narodowego Funduszu Ochrony Środowiska i Gospodarki Wodnej. Uzyskane dane umożliwiły obliczen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…For example, the Wardynka river, in comparison with other watercourses, was subject to occasional maintenance works. Its mountainous character, varied substrate and partially forested catchment allow it to achieve high indices of hydromorphological diversity (Spieczyński et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Wardynka river, in comparison with other watercourses, was subject to occasional maintenance works. Its mountainous character, varied substrate and partially forested catchment allow it to achieve high indices of hydromorphological diversity (Spieczyński et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted a decade ago by Spieczyński et al (2013) showed that in certain sections the Wardynka river was, hydromorphologically, of moderate ecological status, which did not meet the requirements of the Water Framework Directive. Since then, pro-environmental hydrotechnical works have been carried out to restore river longitudinal connectivity for the migration of fish and other The way in which the river valley is delineated also affects the hydromorphological assessment of the watercourse by significantly influencing the HDS and HIR parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Its mountainous character, varied substrate and partially forested catchment make it achieve high indices of hydromorphological diversity. A study conducted a decade ago by Spieczyński et al (2013) showed that the Wardynka river in certain sections hydromorphologically reached moderate ecological status, which did not meet the requirements of the Water Framework Directive. Since then, proenvironmental hydrotechnic works have been carried out to make the catchment clear for the migration of sh and other aquatic organisms, which may have affected the morphological diversity of the watercourse.…”
Section: Discussionmentioning
confidence: 99%